(untitled) (INNOVATIVE ECONOMY, 2021)
Putsenteilo P.R., Dovbush A.V. THE MAIN VECTORS OF ACCOUNTING DEVELOPMENT IN A DIGITAL ECONOMY Purpose. The aim of the article is the analysis of scientific approaches to the interpretation of the peculiarities of the development of digital technologies of modern accounting in the digital economy. Methodology of research. The study was conducted using a dialectical approach to the study of the current state of the digital economy. In the course of the research general and special methods were used, in particular: the analytical method was used in the review of normative sources; the method of classification made it possible to differentiate the main components of the digital economy and accounting, and the method of description ‒ to give them a detailed description; monographic method is used in the study of literature sources on digital economics and accounting, system and analytical ‒ in the processing of information. Findings. It is determined that the digital economy is a communication environment of economic activity on the Internet, the result of transformational effects of new general-purpose technologies in the field of information and communication. It is substantiated that significant technological and informatization shifts, as well as growth of potential of digital economic information space stimulate modernization of accounting science, promote development of methodology and organization of accounting process, actualize the problem of positioning of accounting activity. The basic principles of functioning of the digital accounting platform are revealed, which allow to create the newest electronic systems with a significant number of users. Originality. It has been established that the block-chain is a promising accounting technology that eliminates traditional methods of accounting, documentation, processing, registration, inventory systems, while allowing companies to register both parties to the transaction in a joint book in real time, rather than keeping agreed records of financial transactions separately, private database. Practical value. The obtained results of the study will help increase the efficiency of the formation and development of accounting in a digital economy and will be the basis for further research in this area. Key words: digital economy, information technologies, accounting, digital accounting, block-chain, digital platform, digital technologies.